Focused assessment with sonography for trauma in children after blunt abdominal trauma: A multi-institutional analysis. Issue 2 (August 2017) - Calder, Bennett W.; Vogel, Adam M.; Zhang, Jingwen; Mauldin, Patrick D.; Huang, Eunice Y.; Savoie, Kate B.; Santore, Matthew T.; Tsao, KuoJen; Ostovar-Kermani, Tiffany G.; Falcone, Richard A.; Dassinger, M. Sidney; Recicar, John; et al.
Abstract : Introduction: The utility of focused assessment with sonography for trauma (FAST) in children is poorly defined with considerable practice variation. Our purpose was to investigate the role of FAST for intra-abdominal injury (IAI) and IAI requiring acute intervention (IAI-I) in children after blunt abdominal trauma (BAT). Methods: We prospectively enrolled children younger than 16 years after BAT at 14 Level I pediatric trauma centers over a 1-year period. Patients who underwent FAST were compared with those that did not, using descriptive statistics and univariate analysis; p value less than 0.05 was considered significant. FAST test characteristics were performed using computed tomography (CT) and/or intraoperative findings as the gold standard. Results: Two thousand one hundred eighty-eight children (age, 7.8 ± 4.6 years) were included. Eight hundred twenty-nine (37.9%) received a FAST, 340 of whom underwent an abdominal CT. Ninety-seven (29%) of these 340 patients had an IAI and 27 (7.9%) received an acute intervention. CT scan utilization after FAST was 41% versus 46% among those who did not receive FAST. The frequency of FAST among centers ranged from 0.84% to 94.1%. There was low correlation between FAST and CT utilization (r = −0.050, p < 0.001). Centers that performed FAST at a higher frequency did not have improved accuracy. The test performance of FAST for IAI was sensitivity, 27.8%; specificity, 91.4%; positive predictive value, 56.2%; negative predictive value, 76.0%; and accuracy, 73.2%. There were 81 injuries among the 70 false-negative FAST. The test performance of FAST for IAI-I was sensitivity, 44.4%; specificity, 88.5%; positive predictive value, 25.0%; negative predictive value, 94.9%; and accuracy, 85.0%. Fifteen children with a negative FAST received acute interventions. Among the 27 patients with true positive FAST examinations, 12 received intervention. All had an abnormal abdominal physical examination. No patient underwent intervention before CT scan. Conclusion: As currently used, FAST has a low sensitivity for IAI, misses IAI-I and rarely impacts management in pediatric BAT. LEVEL OF EVIDENCE: Prognostic and epidemiologic study, level II; diagnostic tests or criteria study, level II; therapeutic/care management study, level III. Abstract : Supplemental digital content is available in the text.